ADJUSTABLE NITROOXIDATION TECHNOLOGY FOR LOW ALLOY STEEL - Berdiev Sherzod Alimardonovich (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The article discusses the production of a surface diffusion nitride-oxide layer on low-alloy structural steel with specified structures and properties. To develop a controlled technology for nitro-oxidation of low-alloy carbon steel, the dependences of the composition and structure of the nitrided and oxide layer on the chemical composition of the steel and the technological parameters of the process were studied. Technical iron was used as a model alloy and samples of industrial steel grades 40X, P6M5 and steel 45 were processed. Saturation temperatures were studied in the ranges above and below the eutectoid temperature for the “Fe-N” system and, accordingly, for the “Fe-O” system and it was found that the best structures are at saturation temperatures below the eutectoid